If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = 5x + -4 Reorder the terms: 1 = -4 + 5x Solving 1 = -4 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 1 + -5x = -4 + 5x + -5x Combine like terms: 5x + -5x = 0 1 + -5x = -4 + 0 1 + -5x = -4 Add '-1' to each side of the equation. 1 + -1 + -5x = -4 + -1 Combine like terms: 1 + -1 = 0 0 + -5x = -4 + -1 -5x = -4 + -1 Combine like terms: -4 + -1 = -5 -5x = -5 Divide each side by '-5'. x = 1 Simplifying x = 1
| x/6-2=-6 | | 200/10+2e^3x=4 | | 2(x+8)=3(x+7) | | -1/2x^2+2x+6=0 | | F(x)=x^3+5x^2+1 | | 2y+1/6=3y+5/6 | | 2(T-5)=0 | | 3p+4q=38 | | 3=3x-6 | | 87-2=10x+15 | | 2=5x-3 | | 3.85=5.47 | | 3.85=5.4 | | -4x-6=-30 | | 9m+8n=156 | | 5(x+4)/4=3x-1 | | 5(x+4)/4=3x+1 | | X+(3x+2)=26 | | Y=1/2x-8 | | x-(1+x)+2x=-x+1 | | -11.1=8.1+v/6 | | 375=900-300p | | 2-sec^2(X)=2tan^2(X) | | T/8=13 | | 4x-6*-2=15 | | W^2-6w-66=0 | | 2log(x-1)=5log(y+2) | | (4*5)/5+4=c | | logx+3logy=0 | | 5*4/5+4 | | (10n+10)-10=10 | | 3*-4-6/x=12 |